Repeatability and Phenotypic Correlation Among Semen Quality Traits in Holstein Bulls - Argi Argiris; Siswanto Imam Santoso; Yon Supri Ondho; Edy Kurnianto (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
The purpose of this research was to analysis the value of repeatability and correlation among the traits affecting the production of frozen semen from Holstein’s bull in Indonesia. Repeatability and correlation were calculated based on the data of frozen semen production of 15.699 records from 44 Holstein bulls at Singosari Artificial Insemination Center (SAIC) and 8.935 records from 39 Holstein bulls at Lembang Artificial Insemination Center (LAIC). Repeatability for volume, motility, fresh semen concentration and frozen semen production was evaluated by intraclass correlation method. The repeatability values of LAIC for volume, motility, fresh semen concentration and frozen semen production were 0.60; 0.54; 0.37 and 0.47. The repeatability values of SAIC for volume, motility, fresh semen concentration and frozen semen production were 0.54; 0.30; 0.43 and 0.29. The linear correlation value between volume, motility and fresh semen concentration with the amount of semen produced per collections were 0.41, 0.36, and 0.58. Concentration was the most factors influencing the number of frozen semen produced. The effectiveness of the selection of Holstein's frozen semen producing could be determined by the value of repeatability and the phenotypic correlation among semen quality traits such as volume, motility, concentration and frozen semen production.